Advance care planning for the severely ill in the hospital: a randomized trial. Issue Volume 12:Issue e3(2022) (21st January 2019) - Krones, Tanja; Budilivschi, Ana; Karzig, Isabelle; Otto, Theodore; Valeri, Fabio; Biller-Andorno, Nikola; Mitchell, Christine; Loupatatzis, Barbara
Abstract : Objectives: To investigate the impact of advance care planning (ACP) including decision aids for severely ill medical inpatients. Methods: Single-centre randomised controlled trial at a Swiss university hospital. Patients were randomly assigned (1:1) to receive an extra consultation with the hospital social service or a consultation with in-house facilitators trained according to an internationally established ACP programme. Trial participants with the exception of the observers were fully blinded. 115 competent severely ill adults, their surrogates and their attending physicians were enrolled and followed for 6 months after discharge or 3 months after death. The patient's wishes regarding resuscitation (primary outcome), last place of care and other end-of-life wishes were recorded. Knowledge and respect of the patient's wishes by the surrogates and attending physician were monitored. Results: Compared with controls, 6 months after the intervention, fewer patients wished to be resuscitated or were undecided (p=0.01), resuscitation wishes were documented more frequently (89% vs 64%, p=0.02) and surrogates and/or attending physicians had greater knowledge of the patient's wishes (62% vs 30%, p=0.01). Groups were not different with regard to wishes being fulfilled, with the exception of last place of care being achieved more frequently in the intervention group (29% vs 11 %, p=0.05). Conclusion: ACP including decision aids offered to severely ill medical inpatients leads to greater knowledge, documentation and respect of treatment and end-of-life wishes. Introducing ACP to these patients however may be too late for many patients. Early integration of ACP during the illness trajectory and a broader regional approach may be more appropriate.